1950
DOI: 10.1139/cjr50f-030
|View full text |Cite
|
Sign up to set email alerts
|

The Thiamine and Riboflavin Content of Manitoba Grown Wheat, Oats, and Barley of the 1947 Crop

Abstract: The averages and ranges for thiamine in approximately 250 samples of cereals tested, expressed as μgm. per gm., were: barley 4.2 (3.3–5.7), oats 6.7 (3.8–8.6), wheat 4.5 (3.4–5.9); for riboflavin: barley 1.3 (0.9–1.6), oats 1.3 (1.0–1.7), wheat 1.2 (1.0–1.4). There was a marked increase in the thiamine content of oats over that for 1946—amounting to 0.7 μgm. per gm. Barley and wheat showed slight increases. The values for riboflavin in the three cereals grown in 1947 were about the same as those for the 1946 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1955
1955
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results presented in Table 2 show large variations in vitamer content between different malted cereals. This may be due to cereal varieties and seasons (Davis et al, 1943;O'Donnell and Bayfield, 1960;Robinson et al, 1950) and is shown when the raw barley samples were analyzed for this survey. Six raw barley samples were analyzed, two Gairdner varieties from the 2009 season (4.51 and 4.21 mg/g of thiamine; 0.21 and 0.20 mg/g of riboflavin); two Flagship varieties from the 2009 season (5.93 and 5.51 mg/g of thiamine; 0.23 and 0.24 mg/g of riboflavin) and two Gairdner varieties from the 2010 season (3.12 and 2.95 mg/g of thiamine; 0.17 and 0.18 mg/g of riboflavin).…”
Section: Thiamine and Riboflavin Vitamer Content Of Commercially Avaimentioning
confidence: 96%
See 1 more Smart Citation
“…The results presented in Table 2 show large variations in vitamer content between different malted cereals. This may be due to cereal varieties and seasons (Davis et al, 1943;O'Donnell and Bayfield, 1960;Robinson et al, 1950) and is shown when the raw barley samples were analyzed for this survey. Six raw barley samples were analyzed, two Gairdner varieties from the 2009 season (4.51 and 4.21 mg/g of thiamine; 0.21 and 0.20 mg/g of riboflavin); two Flagship varieties from the 2009 season (5.93 and 5.51 mg/g of thiamine; 0.23 and 0.24 mg/g of riboflavin) and two Gairdner varieties from the 2010 season (3.12 and 2.95 mg/g of thiamine; 0.17 and 0.18 mg/g of riboflavin).…”
Section: Thiamine and Riboflavin Vitamer Content Of Commercially Avaimentioning
confidence: 96%
“…Several authors (Davis et al, 1943;Robinson et al, 1950;Voss and Piendl, 1978) have investigated vitamin changes throughout the malting process; however these studies were performed on a limited range of barley and malts. In order to provide further clarification with regard to thiamine and riboflavin vitamer content in malt, a simple and efficient method for their analysis in malt was developed and employed to determine the vitamer content in a wide range of malts.…”
Section: Introductionmentioning
confidence: 97%